2017
DOI: 10.1097/mog.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Colonic ischemia

Abstract: Colonic ischemia is a common cause of lower abdominal pain and hemorrhage among the elderly typically occurring in the aftermath of an event which led to hypoperfusion of the colon. For most affected individuals the ischemia is reversible and clinical course benign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…GIisch is among the most lethal gastrointestinal complications after cardiac surgery (14). Among the mechanisms of GIisch, NOMI has been reported to predominate among ICU patients (3,4,15) in keeping with our data. NOMI is characterized by the triad of low cardiac output and/or hypotension, peripheral-artery and mesenteric atheroma, and extraintestinal organ-function impairments due to hypoperfusion and most often involving the liver and kidney (4).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…GIisch is among the most lethal gastrointestinal complications after cardiac surgery (14). Among the mechanisms of GIisch, NOMI has been reported to predominate among ICU patients (3,4,15) in keeping with our data. NOMI is characterized by the triad of low cardiac output and/or hypotension, peripheral-artery and mesenteric atheroma, and extraintestinal organ-function impairments due to hypoperfusion and most often involving the liver and kidney (4).…”
Section: Discussionsupporting
confidence: 90%
“…The distribution of bowel segments involved in our patients is also in accordance with other studies (4,16). The major site was the colon with typically results from a global reduction in blood flow (15). Ischemia of the colon is usually associated with a rapid perforation (1).…”
Section: Discussionmentioning
confidence: 90%
“…However, it was later found that intraluminal pressures only reach 8–10 cm H 2 O in simple obstruction and are not high enough to cause transmural ischemia in the gut ( Shikata et al, 1983 ; Summers and Lu, 1991 ). Even in the case of ischemia colitis, ischemic change is typically caused by a global reduction in blood flow to the colon, not by local obstructive lesions ( Oglat and Quigley, 2017 ). Nevertheless, blood supply can be compromised through external compression of the bowel or its mesentery by severe adhesions, torsion, or intussusception.…”
Section: Acute Abdominal Pain In Bowel Obstructionmentioning
confidence: 99%
“…Acid-sensitive ion channels (ASIC), TRPV1, and P2X3 are among many of the chemical receptors in the sensory nerve endings ( Bielefeldt, 2006 ; Brierley and Blackshaw, 2006 ). Reviews on inflammation and ischemia associated abdominal pain can be found elsewhere ( Vermeulen et al, 2014 ; Feuerstadt and Brandt, 2015 ; Oglat and Quigley, 2017 ).…”
Section: Acute Abdominal Pain In Bowel Obstructionmentioning
confidence: 99%
“…Ischemic colitis is the most common form of vascular injury to the gastrointestinal tract [1]. The most common reason for colonic ischemia is hypoperfusion as compared to thrombotic and embolic events accounting for most vascular insults to the small bowel [2]. Occurrence is typically segmental with left-sided lesions involving the water-shed regions such as the splenic flexure, descending colon, and sigmoid colon.…”
Section: Introductionmentioning
confidence: 99%